PERANAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH YAYASAN MAHANAIM KOTA BEKASI - Oentoeng, Irvan F. C.; Riady, Hanes (Universitas muhammadiyah palembang, 2013)
This research is related to the factors affecting the teacher’s performance in Mahanaim School. This research is aimed to: 1) investigating the effect of Principal’s Role toward theperformance of Mahanaim school’s teachers, 2) investigating the effect of work motivation toward the performance of Mahanaim school’s teachers, and 3) investigating the effect ofPrincipal’s Role toward the work motivation of Mahanaim School’s teachers. The methodused is causality method. The number of population used is 109 teachers from MahanaimSchool (Kindegarten, Elementary, Junior, Senior and Vocational High School). The data collected in this research is primarily by questionnaires. The data is analyzed with pathanalysis model. The research findings shows that simultaneously components of Principal’s Role (X1) and work motivation (X2) affect significantly to the performance of Mahanaim School’s Teachers (Y) in which R=0,504 and R square= 0,341. The most dominant factor toward the performance of Mahanaim School’s Teachers is the component of work motivation.